KONSTRUKSI TES KEBAHASAAN UAS SD DI KABUPATEN MADIUN - Nur Samsiyah; Apri Kartika Sari; Chrisna Emilia (Universitas PGRI Madiun, 2015)
Language learning is aimed to achieve proficiency properly. To achieve objectives of language learning cannot be separated from aspects of grammar. One way to achieve the grammatical aspect is by using a test. The purpose of language test is ability and skill in language not knowledge about language. Range of aspects are measured based on the types of tests used in the test questions at the end of the learning/ formative. This research aimed to determine language aspects tested at the end of each semester. This study used a qualitative approach and data sources in the form of the exam end of semester 1 and 2 grade 1 to grade 6. Techniques of data collection is done by collecting data source in the field and read the data source. Data analysis phase consists of three stages: data reduction, classification, presentation of data and drawing conclusions. The results showed there were aspects of language such as phonology, morphology aspect which consists of free and bound morpheme, the process of reduplication or repetition, syntactic aspects that form phrases and sentences as well as aspects such as semantic meaning.